Antiretroviral Therapy Adherence Support: Recommendations and Future Directions. (March 2013) - Amico, K. Rivet; Orrell, Catherine
Dramatic increases in the evidence-base for intervention approaches to support antiretroviral therapy (ART) adherence have resulted in numerous reviews, syntheses, and guidelines/recommendations. This review characterizes the current state of the literature and identifies areas in need of additional targeted focus to better align research and practice. Leading recommendations for the process of intervention development (relevant to both rigorous research and real-world intervention planning) and strategies to consider in working with individuals, communities, and systems are provided. In order to move systematically toward the identification of what kinds of interventions work best for whom and when, attending to both intervention outcomes and "drivers" of observed effects or lack of effects in controlled research is critically important. Further, evidence emerging from practice should be aggressively added to research agendas to promote better synergies between the practice and research communities.